Means of Employing Radiation Nulls in Filtennas: A Review - A. Veerabhadra Rao; Gopi Ram (IEEE Access)
In this paper, methods for improving frequency selectivity in filter antennas by employing controllable radiation nulls (RN) are reviewed. Radiation nulls in the Gain graph help in improving the rejection of out-of-band frequencies. The majority of the designs reviewed in this paper use substrate-integrated waveguide (SIW) technology. Some of the methods of generating RNs include: loading filtenna with slots or shorting pins, using proper design of multi-signal path between source and load, employing electric and magnetic mixed-coupling, embedding filtering structures, parasitic elements, employing filtering action in the feed network. Certain designs achieve more than two radiation nulls which give even better selectivity.